National Trends in Utilization and 1-Year Outcomes with Transplantation of HCV-Viremic Kidneys - Potluri, Vishnu S; Goldberg, David S; Mohan, Sumit; Bloom, Roy D; Sawinski, Deirdre; Abt, Peter L; Blumberg, Emily A; Parikh, Chirag R; Sharpe, James; Reddy, K Rajender; Molnar, Miklos Z; Sise, Meghan; et al. (Journal of the American Society of Nephrology, 2019)
Recent pilot trials have demonstrated the safety of transplanting HCV-viremic kidneys into HCV-seronegative recipients. However, it remains unclear if allograft function is impacted by donor HCV-viremia or recipient HCV-serostatus. We used national United States registry data to examine trends in HCV-viremic kidney use between 4/1/2015 and 3/31/2019. We applied advanced matching methods to compare eGFR for similar kidneys transplanted into highly similar recipients of kidney transplants. Over time, HCV-seronegative recipients received a rising proportion of HCV-viremic kidneys. During the first quarter of 2019, 200 HCV-viremic kidneys were transplanted into HCV-seronegative recipients, versus 69 into HCV-seropositive recipients, while 105 HCV-viremic kidneys were discarded. The probability of HCV-viremic kidney discard has declined over time. Kidney transplant candidates willing to accept a HCV-seropositive kidney increased from 2936 to 16,809 from during this time period. When transplanted into HCV-seronegative recipients, HCV-viremic kidneys matched to HCV-non-viremic kidneys on predictors of organ quality, except HCV, had similar 1-year eGFR (66.3 versus 67.1 ml/min per 1.73 m , =0.86). This was despite the much worse kidney donor profile index scores assigned to the HCV-viremic kidneys. Recipient HCV-serostatus was not associated with a clinically meaningful difference in 1-year eGFR (66.5 versus 71.1 ml/min per 1.73 m , =0.056) after transplantation of HCV-viremic kidneys. By 2019, HCV-seronegative patients received the majority of kidneys transplanted from HCV-viremic donors. Widely used organ quality scores underestimated the quality of HCV-viremic kidneys based on 1-year allograft function. Recipient HCV-serostatus was also not associated with worse short-term allograft function using HCV-viremic kidneys.